State Space Initiation for Blind Mobile Terminal Position Tracking. (29th November 2007) - Algeier Algeier, Vadim Vadim; Demissie Demissie, Bruno Bruno; Koch Koch, Wolfgang Wolfgang; Thomä Thomä, Reiner Reiner
Abstract : Blind localization and tracking of mobile terminals in urban scenarios is an important requirement for offering new location-based services, handling emergency cases of nonsubscribed users, public safety, countering IEDs, and so forth. In this context, we propose a track-before-detect scheme taking explicitly advantage of multipath propagation in an urban terrain by using a priori information about the known locations of the main scattering objects such as buildings. This information is made available for localization and tracking by a real-time ray tracing technique based on a 2D geographic database. This allows the prediction of the directional and temporal structure of the received multipath components for an arbitrary transmitter position. We consider a single observing station where the direction and the relative time of arrival of the received multipath components can be estimated by an antenna array. By a likelihood function, which is algorithmically defined for a randomly distributed set of potential transmitter positions, these measurements are compared with those being expected by ray tracing. This likelihood function is the key component of a track-before-detect scheme providing initial state estimates for mobile transmitter tracking using a particle filtering technique.